- Download PDF
1 Answer | Add Yours
The graph of the curve y = ax^2 + 2x + 4 and the line y + x = 6 intersect at only one point.
From y + x = 6, the value of the dependent variable is y = 6 - x.
Equating this to y = ax^2 + 2x + 4 gives:
6 - x = ax^2 + 2x + 4
=> ax^2 + 3x - 2= 0
Any quadratic equation ax^2 + bx + c = 0 has two equal roots if `b^2 - 4*a*c = 0` . Substitute the values for a, b and c from ax^2 + 3x - 2 = 0.
`3^2 + 4*a*2 = 0 => a = -9/8`
The curve y = -9x^2/8 + 2x + 4 intersects the line y + x = 6 once.
The required value of a = -9/8
We’ve answered 323,979 questions. We can answer yours, too.Ask a question